Controlling the charge carrier dynamics by modulating the orientation diversity of perovskites. (11th March 2022) - Cha, Wonhee; Cha, Won-Young; Noh, Insub; Seki, Shu; Ohkita, Hideo; Kim, Dongho
Abstract : Photo-induced charge carrier dynamics over a wide time domain from sub-nanoseconds to microseconds,   via  time-correlated single photon counting and flash photolysis time-resolved microwave conductivity measurements. Abstract : Organic–inorganic halide perovskite-based solar cells have drastically improved in recent decades, with power conversion efficiencies of up to 25%. However, the fundamental photophysical properties underlying the outstanding performance have not been elucidated. Herein, we investigate the detailed photo-induced charge carrier dynamics over a wide time domain from sub-nanoseconds to microseconds, via time-correlated single photon counting and flash photolysis time-resolved microwave conductivity measurements. The structure of the perovskites significantly influences the whole periodic dynamics of mobile charge carriers. The mobility was considerably larger and the extraction to the transporting layer occurred more effectively in perovskites with higher orientation diversity than in highly oriented perovskites, resulting in higher efficiencies. The relationship between the orientation diversity of perovskites and their power conversion efficiency was investigated. Our work will be beneficial for the development of high-efficiency solar cell devices.